PENGARUH MEDIA SOSIAL DALAM MEMBANGUN OPINI PUBLIK - Muhammad Qadri (Qaumiyyah: Jurnal Hukum Tata Negara, 2020)
This paper discusses how the influence of social media in building public opinion. The use of social media has a positive impact in the process of social, political and economic interactions. The use of social media also makes it easy to access various information needed, makes it easy to communicate rarely far away and social media can also be a tool to make new friends. Of the various positive impacts of social media, it turns out that it also has a negative impact if users cannot properly filter news or information that contains divisions, hoaxes or fake news, sara issues, religion and others that are carried out by people who are not responsible, then it can cause chaos which will certainly split the unity.